2022
DOI: 10.1038/s41398-022-02035-4
|View full text |Cite
|
Sign up to set email alerts
|

Time moderates the interplay between 5-HTTLPR and stress on depression risk: gene x environment interaction as a dynamic process

Abstract: The serotonin-transporter-linked promoter region (5-HTTLPR) has been widely investigated as contributing to depression vulnerability. Nevertheless, empirical research provides wide contrasting findings regarding its involvement in the etiopathogenesis of the disorder. Our hypothesis was that such discrepancy can be explained considering time as moderating factor. We explored this hypothesis, exploiting a meta analytic approach. We searched PubMed, PsychoINFO, Scopus and EMBASE databases and 1096 studies were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…On the one hand, Bleys et al [ 42 ] stated that their meta-analysis provided new evidence for the robustness of the interaction between stress and 5-HTTLPR in depression, but on the other hand, another meta-analysis published in the same year by Culverhouse et al [ 43 ] found no proof of a strong interaction between stress and the 5-HTTLPR genotype thats would contribute to the development of depression. One of the latest meta-analyses about the interaction among 5-HTTLPR, stress, and depression also added a temporal dimension, which resulted in a three-way interaction: gene x environment x time [ 44 ]. This meta-analysis revealed that the 5-HTTLPR and stress interaction was a dynamic process, producing different effects at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, Bleys et al [ 42 ] stated that their meta-analysis provided new evidence for the robustness of the interaction between stress and 5-HTTLPR in depression, but on the other hand, another meta-analysis published in the same year by Culverhouse et al [ 43 ] found no proof of a strong interaction between stress and the 5-HTTLPR genotype thats would contribute to the development of depression. One of the latest meta-analyses about the interaction among 5-HTTLPR, stress, and depression also added a temporal dimension, which resulted in a three-way interaction: gene x environment x time [ 44 ]. This meta-analysis revealed that the 5-HTTLPR and stress interaction was a dynamic process, producing different effects at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the combination of psychotherapy with antidepressants has been shown to be more effective than the drug alone . The key role of context is increasingly demonstrated also in studies concerning genetic polymorphisms affecting serotonin levels, such as the serotonin-transporter-linked promoter region (5HTTLPR) polymorphism, that makes individuals either more vulnerable or capable to recover from depression, according to their living conditions (Delli Colli et al, 2022). As a final telling example from rodent studies, a testosterone surge in the same individuals induces opposite behavioral outcomes according to social context, either facilitating prosocial responses if administered during affiliative encounters, or triggering aggression if administered during fights (Kelly et al, 2022).…”
Section: Context Drives Treatment Outcome: Rethinking Neuropsychophar...mentioning
confidence: 99%
“…By contrast, contextual factors, such as the living conditions or psychotherapeutic approaches, drive such change toward a beneficial outcome. Indeed, high plasticity is therapeutic in a favorable context [1][2][3] . For instance, the efficacy of plasticity-enhancing treatments such as selective serotonin reuptake inhibitors (SSRIs), psychedelics and ketamine-in promoting recovery from illness has been shown to be, at least in part, dependent on their combination with favorable environmental conditions [4][5][6][7][8] .…”
Section: Mainmentioning
confidence: 99%